Deltamethrin induces liver fibrosis in quails via activation of the TGF-β1/Smad signaling pathway. (April 2020) - Han, Bing; Lv, Zhanjun; Zhang, Xiaoya; Lv, Yueying; Li, Siyu; Wu, Pengfei; Yang, Qingyue; Li, Jiayi; Qu, Bing; Zhang, Zhigang
Abstract: Deltamethrin (DLM) is an important member of the pyrethroid pesticide family, and its widespread use has led to serious environmental and health problems. Exposure to DLM causes pathological changes in the liver of animals and humans and can lead to liver fibrosis. However, the mechanism of DLM-induced liver fibrosis remains unclear. Therefore, to address its potential molecular mechanisms, we used both in vivo and in vitro methods. Quails were treated in vivo by intragastric administration of different concentrations of DLM (0, 15, 30, or 45 mg kg −1 ), and the chicken liver cancer cell line LMH was treated in vitro with various doses of DLM (0, 50, 200, or 800 μg mL −1 ). We found that DLM treatment in vivo induced liver fibrosis in a dose-dependent manner through the promotion of oxidative stress, activation of transforming growth factor-β1 (TGF-β1) and phosphorylation of Smad2/3. Treatment of LMH cells with different concentrations of DLM similarly induced oxidative stress and also decreased cell viability. Collectively, our study demonstrates that DLM-induced liver fibrosis in quails occurs via activation of the TGF-β1/Smad signaling pathway. Graphical abstract: Image 1 Highlights: Chronic exposure of deltamethrin (DLM) induces liver fibrosis in quail. DLM induces fatty degeneration of liver in quail. DLM induces oxidative stress in LMH cells. Oxidative stress is a key of DLM-induced liver fibrosis.